Selling war : the British propaganda campaign against American "neutrality" in World War II - Cull, Nicholas John (Oxford University Press, 1995)
British propoganda brought America to the brink of war, and left it to the Japanese and Hitler to finish the job.' So concludes Nicholas Cull in this absorbing study of how the United States was transformed from isolation to belligerence in the years before the attack on Pearl Harbor. From the moment it realized that all was lost without American aid, the British Government employed a host pf persuasive tactics to draw the U.S. to its rescue. With the help of talents as varied as those of matinee idol Leslie Howard, Oxford philosopher Isaiah Berlin and society photographer Cecil Beaton, no section of America remained untouched and no method - from Secret Service intrigue to the publication of horrifying pictures of Nazi attrocities - remained untried. A fascinating story of how a foreign country promoted America's involvement in its greatest war, Selling War will appeal to all those interested in the modern cultural and political history of Britain in the twentieth century and World War II. The Kirkus Review wrote, 'A valuable study of how British propoganda helped to bring the U.S. into W.W. II ...